2020
DOI: 10.1039/d0ra02257h
|View full text |Cite
|
Sign up to set email alerts
|

Highly luminescent polyethylene glycol-passivated graphene quantum dots for light emitting diodes

Abstract: We prepared blue-photoluminescent polyethylene glycol GQDs (PEG-GQDs) through PEG surface passivation. The PL intensity was stronger than that of pristine GQDs. These were then used as LED emitters and the fluorescence mechanism was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Therefore, it was confirmed that the GQDs can be used for tracing the pathway of the materials and there were no distinct differences in an optical property before and after PEGylation. The detailed PL properties are reported in previous papers [35,41].…”
Section: Peg-graphene Quantum Dot (Peg-gqds) Characterizationmentioning
confidence: 99%
“…Therefore, it was confirmed that the GQDs can be used for tracing the pathway of the materials and there were no distinct differences in an optical property before and after PEGylation. The detailed PL properties are reported in previous papers [35,41].…”
Section: Peg-graphene Quantum Dot (Peg-gqds) Characterizationmentioning
confidence: 99%
“…8 For example, Kim et al constructed blue photoluminescent polyethylene glycol GQDs (PEG-GQDs) with luminescence exceeding 800 cd m −2 . 9 In addition, Qu et al reported S,N-GQDs with three excitation wavelength-independent emissions and applications in visible light H 2 production and bioimaging. 10 We recently used citric acid (CA) as a carbon source, sodium hydrosulfide (NaHS) as a sulfur source, and O -phenylenediamine (OPD) as a nitrogen source to easily synthesize S,N-GOQDs with stable electroluminescence, photoluminescence, and photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported the synthesis of FGQDs by chemical oxidation, electrochemical preparation, and hydrothermal methods. However, these methods are usually performed under strongly acidic conditions, which require a prolonged washing step. Furthermore, for the surface passivation and functionalization of GQDs, multiple synthesis processes such as heat treatment and deep coating are required, which are costly and time-consuming. , Therefore, it is necessary to develop a one-step synthetic method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for the surface passivation and functionalization of GQDs, multiple synthesis processes such as heat treatment and deep coating are required, which are costly and time-consuming. 27,28 Therefore, it is necessary to develop a one-step synthetic method.…”
Section: Introductionmentioning
confidence: 99%